Measuring competitiveness in tourism entrepreneurial ecosystems: model, methodology, y evaluation tool - Garcia Reinoso, Nelson (2024)
Introduction: The competitiveness of tourism entrepreneurs has scarcely explored in the historiographical literature, despite its importance for the development of the sector. Properly evaluating this competitiveness is crucial for formulating effective strategies that drive sustainable tourism growth. Objective: To develop a model, methodology, y comprehensive tool to evaluate the competitiveness of the tourism entrepreneurial ecosystem using specific indicators. Method: A detailed methodology was implemented that describes the model, its indicators, y proposes a tool for data collection. This methodology focuses on three crucial areas, which are: demographic information, business perceptions of the ecosystem, y key business y entrepreneurial indicators. The tool applies structured surveys y qualitative y quantitative analysis techniques to obtain a comprehensive view of the ecosystem. Results: The expected results allow for an exhaustive evaluation of how entrepreneurs perceive y respond to their operating environment. Strengths and opportunities for improvement within the entrepreneurial ecosystem are identified, providing valuable data for strategic decision-making. This facilitates the formulation of public policies y business strategies that promote the competitiveness y sustainability of tourism. Conclusions: This article provides a methodological guide to identify, measure, y analyze the key factors of competitiveness in tourism ventures. The implementation of the proposed model y tool allows for an accurate diagnosis of the entrepreneurial ecosystem, thus promoting the sustainable development of the tourism sector.